(untitled) (American Journal of Education and Technology, 2023)
Despite efforts made to improve rural infrastructural development over time, many rural infrastructural projects in the rural Mezam Division have remained of poor quality. This paperset out t make an evaluation of the challenges faced by the local population in the Mezam Division and the coping strategies they have adopted to cope with the rural under development. 260 questionnaires were distributed and 210 were obtained. 30 interviews were conducted with rural dwellers, NGOs, community-Based Associations, and state administrators three focus group discussions were organized with 8 members, bringing the total to 24 participants. Multivariate analysis was utilized to establish the framework for judging the quality of rural infrastructural projects and to identify the various coping strategies in the Rural Mezam Division.Data have been analysed both qualitatively and quantitatively; and have been presented on figures, tables, and photos.Findings revealed that rural infrastructure projects in the Rural Mezam Division are often implemented in challenging environments such as a poor administrative system, scarcity of skilled labour force, low institutional capacity, and high levels of mismanagement. The various development sectors such as agriculture, transport, education and health sectors are affected negatively which has led to rural underdevelopment. As such, the rural people who are the main beneficiaries of rural infrastructure have adopted different coping strategies in the different development sectors in order to sustain their lives. Furthermore, the paper holds that the way forward is for the ruralcouncils to be made autonomous so that they can raise revenue through taxes and use the finances for rural development.